Digitally Mediated Problem-based Learning Integrating Aneuk Jamee Cultural Values to Enhance Computational Thinking and Cultural Identity in Primary Education. - Mardhatillah; Khotimah, Khusnul; Sari, Zihan Novita; Kamarudin, Nurzatulshima; Dony, Novrian; Huzaimah, Cempa; Diana, Ilfi Nur (Pertanika Journal of Social Sciences & Humanities, 2026)
This study aimed to develop a problem-based learning model that integrates Aneuk Jamee cultural values through the use of digital platforms to improve the quality of learning in elementary schools. The method used is research and development (R&D) based on the Plomp approach, which includes the stages of initial investigation, design, development, formative evaluation, implementation, and dissemination of the product. The participants were thirty fourth-grade students (N=30; aged 9-11 years) in a public elementary school in Malang, Indonesia. The research instruments included learning tools, student books, activity sheets, and computational thinking ability tests. The results show that integrating local culture into learning increases motivation, active participation, and students' understanding of the material and cultural values. This model has also been proven to support the development of 21st century skills such as critical thinking, creativity, and collaboration. Expert validation indicated that the developed tools were highly feasible for use, and trial results showed a significant improvement in students' computational thinking abilities. This research makes a tangible contribution to innovation in culturally based and contextually relevant digital technology learning while strengthening students' cultural identity in the global era.